The grim steeper - Rue, Gretchen (Rue, Gretchen. Witches' Brew mystery ;, 2024)
"Amateur witch Phoebe Winchester is excited to host her first big author event at the Earl's Study, her book and tea store. The author, Sebastian Marlow, is a famous birder excited to put Raven Creek on the map for his rediscovery of a presumed-extinct bird. When Sebastian is found dead before his planned bird hike, where he expected to prove the existence of the bird to fellow birding enthusiasts, it's obvious someone wanted him to be extinct, too."--